Delayed Presentation of Traumatic Right-Sided Diaphragmatic Hernia after Abdominoplasty - Caroline C. Jadlowiec; Lois U. Sakorafas (Case Reports in Surgery)
Traumatic diaphragmatic hernias are rare and challenging to diagnose. Following trauma, diagnosis may occur immediately or in a delayed fashion. It is believed that left traumatic diaphragmatic hernias are more common as a result of the protective right-sided anatomic lie of the liver. If unrecognized, traumatic diaphragmatic injuries are subject to enlarge over time as a result of the normal pressure changes observed between the thoracic and abdominal cavities. Additionally, abrupt changes to the pressure gradients, such as those which occur with positive pressure ventilation or surgical manipulation of the abdominal wall, can act as a nidus for making an asymptomatic hernia symptomatic. We report our experience with a delayed traumatic right-sided diaphragmatic hernia presenting with large bowel incarceration two months after abdominoplasty. In our review of the literature, we were unable to find any reports of delayed presentation of a traumatic right-sided diaphragmatic hernia occurring acutely following abdominoplasty.